(untitled) (Nexo Revista Científica, 2021)
Mechanical and pneumatic seed drills of both domestic and foreign production are used in Russian farms. They are equipped with a mechanical drive of working tools and an electronic seeding control system. Due to the slipping of the wheels or the breakage of the chains, the sowing of seeds in individual seed dispensers interrupts. According to the results of laboratory and bench-scale studies in respect to soybean seeds, the required power for the electric drive of one seed dispenser was determined, which, depending on the disk rotation speed from 10 to 60 rpm, ranged from 30 to 120 W. By calculation, using the analytical expression, the power, required for the fan drive of a 12-row seed drill, was determined, which, depending on the disk rotation speed, ranged from 1.6 to 2.47 kW. A condition is formulated, which will eliminate the probability of shifting and rolling seeds along the furrow after their fall out of the sowing disc rotating in the opposite direction to the movement of the seeder unit, provided correspondence of the linear speed of the sowing disc and the speed of the seeder unit (the effect of zero overlaps). In this case, the trajectory length of the seeds falling to the furrow should be consistent with the speed of the seeder unit and the seeding rate according to the proposed expression.